ALGEBRAIC ASPECTS OF CRYPTOGRAPHY - NEAL KOBLITZ (NEW DELHI SPRINGER, 2004)
This is a textbook in cryptography with emphasis on algebraic methods. It is supported by many exercises (with answers) making it appropriate for a course in mathematics or computer science.
Keywords: CRYPTOGRAPHY -- CODING THEORY -- ELLIPTIC CURVES